SOLAR PANEL APPLICATION IN KOI SPAWNING PONDS FOR IMPROVED FISH FARMING PRODUCTIVITY IN TULUNGAGUNG - Adiwidodo, Satworo; Asrori, Asrori; Witono, Kris; Fakhruddin, Muhammad; Pranoto, Bayu; Yudiyanto, Eko; Sulistyono, Sulistyono (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The Community Service (CS) program took place in Sumberingin Kidul Village, Ngunut District, Tulungagung Regency, approximately 100 km southwest of Malang City. The target group for this program includes small and medium enterprises (SMEs) engaged in koi fish spawning. Our partners face several challenges, primarily the reliance on aeration pumps powered by the national electricity grid (PLN) to supply oxygen to the ponds. The program aimed to install a 100 Wp solar panel system to generate clean energy for a low-voltage aeration pump, helping to maintain optimal oxygen levels in the pond and supporting healthy fish growth. The program successfully implemented this solar-powered aerator pump system in the pond area, providing an innovative, sustainable solution that empowers the community by integrating science and technology into fisheries. It is hoped that this program will inspire other fish farmers in Tulungagung and surrounding areas to adopt similar sustainable practices.